Measurement of Auroral Electric Fields with an Antarctic Sounding Rocket S-310JA-7. 2.AC Electric Field - Yamagishi, Hisao; Fukunishi, Hiroshi; Hirasawa, Takeo; Ogawa, Toshio (1981)
P(論文) A sounding rocket with double-probes for DC electric field and AC electric field (5-220Hz band) measurement was launched from Syowa Station in Antarctica around the onset time of an intense auroral substorm. The rocket first encountered a poleward expanding auroral arc, where intense (1.4mV/m) and broad band electric field fluctuations were measured around the arc at the altitude of 105-128km. The rocket then moved across an equatorward drifting arc, where narrow-band electric field fluctuations around 40Hz were measured at the altitude of ∿190km. Considering the DC electric field data and the electron density gradient observed on the same rocket, it is likely that the former fluctuation is due to drift waves or ion acoustic waves excited by the cross-field type or two-stream type plasma instability, while the latter is due to electrostatic ion cyclotron waves excited by fieldaligned currents. departmental bulletin paper